2003
DOI: 10.1086/377490
|View full text |Cite
|
Sign up to set email alerts
|

The Coronae of AR Lacertae

Abstract: We observed the coronally active eclipsing binary AR Lac with the High Energy Transmission Grating on Chandra for a total of 97 ks, spaced over five orbits, at quadratures and conjunctions. Contemporaneous and simultaneous EUV spectra and photometry were also obtained with the Extreme Ultraviolet Explorer. Significant variability in both X-ray and EUV fluxes were observed, dominated by at least one X-ray flare and one EUV flare. We saw no evidence of primary or secondary eclipses, but exposures at these phases… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
71
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 46 publications
8
71
0
Order By: Relevance
“…The results also confirm a similar behavior for  1 Ori A and E. This means the bulk of the X-ray emission in the bright Orion Trapezium stars is not compatible with any form of instabilities in a line-driven wind. In fact, these stars seem to be of a hybrid nature where only a small fraction of the X-rays are produced in wind shocks; a larger fraction shows a magnetic origin and bears striking similarities to the hard X-ray emission pattern observed in stars with active coronae (Huenemoerder et al , 2003.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The results also confirm a similar behavior for  1 Ori A and E. This means the bulk of the X-ray emission in the bright Orion Trapezium stars is not compatible with any form of instabilities in a line-driven wind. In fact, these stars seem to be of a hybrid nature where only a small fraction of the X-rays are produced in wind shocks; a larger fraction shows a magnetic origin and bears striking similarities to the hard X-ray emission pattern observed in stars with active coronae (Huenemoerder et al , 2003.…”
Section: Discussionmentioning
confidence: 83%
“…This may not be necessary. As an interesting analogy, the DEMs recently deduced from X-ray emission form active coronae in cool stars such as AR Lac (Huenemoerder et al 2003) and II Peg ) appear very similar during flares, where in addition to a small low-temperature peak one or more strong high-temperature peaks evolve. The nature of the spectra in these cases are of striking similarity to the ones that we observe in the Orion Trapezium with strong continua and unresolved lines.…”
Section: Magnetically Confined Windsmentioning
confidence: 87%
“…This conclusion is reinforced by the much more favorable comparison of the results of the recent Chandra and XMMNewton studies of AB Dor-this work compared with that of Güdel et al (2001) and Sanz-Forcada et al (2003). Audard et al (2004), Huenemoerder et al (2003), and SanzForcada et al (2003 have recently reported, for V824 Ara, AR Lac, and AB Dor, respectively, higher values for abundances of Al, Ca, and Na than for elements with slightly higher FIPs, suggesting a schism in the strictly inverse FIP effect scheme. In particular, Sanz-Forcada et al (2003) obtained different values of Ca abundance for AB Dor, including a very high Mewe et al (1996); (2) value of ½Ca=H ¼ 0:62 derived from the high-resolution RGS spectrum.…”
Section: Coronal Abundancesmentioning
confidence: 85%
“…Griffiths & Jordan (1998) estimated a coronal plasma density of 5 × 10 11 cm −3 based on Fe XXI lines. Huenemoerder et al (2003) also found tentative evidence for high plasma densities on the order of log n e ∼ 11 cm −3 using lines from the He-like ions of O and Ne formed around 2-4 × 10 6 K. This result was confirmed by Testa et al (2004a), who found log n e = 12.5 ± 0.5 cm −3 from He-like Mg formed at slightly hotter temperatures of ∼ 6×10 6 K (see also Ness et al 2004). Testa et al (2004a) also analysed the Chandra spectra of several other active binaries and found similar high densities to generally characterise the coronae of very active stars.…”
mentioning
confidence: 59%